The correct option is: 20
Explanation
The expression [tex](x+j)(x-j)(x-k)[/tex] can be rewritten as [tex]x^3-5x^2-4x+t[/tex]
That means: [tex](x+j)(x-j)(x-k)= x^3-5x^2-4x+t[/tex]
Now simplifying the left side, we will get....
[tex](x+j)(x-j)(x-k)= x^3-5x^2-4x+t\\ \\ (x^2-j^2)(x-k)= x^3-5x^2-4x+t\\ \\ x^3-kx^2-j^2x+j^2k= x^3-5x^2-4x+t[/tex]
Now comparing the co-effcients of like terms in left and right side, we will get.....
[tex]k=5, j^2=4 \\ \\ and\\ \\ t=j^2k\\ \\ So, t= (4)(5) =20[/tex]
Thus, the value of 't' will be 20.